BIOCHEMICAL COMPOSITION AND THE NUTRITIVE VALUE OF ZOOPLANKTER OF A FRESH WATER LAKE (VELACHERY) - RAMARANI, S.; RAMALINGAM, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The biological analysis of three principal metabolites was carried out in the zooplankter collected from Velachery lake, Chennai. Protein contents remained high, when compared to carbohydrates and fatty acids. The organic matter formed by these plankter may be responsible for the viability of the above lake ecosystem.